2020
DOI: 10.1007/s12288-020-01278-9
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of the BMI-1 and BAALC Genes in Adult Patients with Acute Myeloid Leukemia

Abstract: The aim of this work is to investigate the different expression patterns of B cell-specifics moloney murine Leukemia virus integration site-1 (BMI-1) and brain and acute leukemia, cytoplasmic (BAALC) genes, their prognostic and clinical significance in newly diagnosed cytogenetically heterogenous adult acute myeloid leukemia patients. BMI-1 and BAALC expression was detected in the bone marrow of patients using quantitative real-time reverse transcription polymerase chain reaction with cut off value set at 50th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In some of them, the authors found a trend that high BAALC expressers are younger age than the low expressers [10]. In an analysis from Shafik et al a statistical significance between BAALC and age, CD34 expression, and close to significant results with some of FAB sub-groups was found [27].…”
Section: Correlation Of Bаalc Overexpression With Some Clinical Labor...mentioning
confidence: 94%
See 1 more Smart Citation
“…In some of them, the authors found a trend that high BAALC expressers are younger age than the low expressers [10]. In an analysis from Shafik et al a statistical significance between BAALC and age, CD34 expression, and close to significant results with some of FAB sub-groups was found [27].…”
Section: Correlation Of Bаalc Overexpression With Some Clinical Labor...mentioning
confidence: 94%
“…Therefore, BAALC overexpression and the FLT3 mutation is an objects of many studies. Some of them [14,23,27,28], failed to find a link between BAALC and FLT3-ITD, but opposing this conclusion, other authors provide results concluding that there is a strong correlation between high BAALC expression and the FLT3-ITD mutation [10,29,30].…”
Section: Correlation Of Bаalc Overexpression With Some Clinical Labor...mentioning
confidence: 96%